Ecotourism of Kajigelem Craft Villages: Preserving Nature - Thriving Creative Economy - Astutiningsih, Sri; Hasan, Renta Vulkanita (KnE Social Sciences, 2022)
Covid-19, whose first case was discovered in early March 2020 in Indonesia, has had a tremendous impact on various sectors of life, including the creative economy. Therefore, any proposed solution should be implemented logically and consistently by all stakeholders. As one of the stakeholders, the researchers propose to investigate the possibilities that can be applied to overcome problems in the creative economy sector. The Kajigelem craft villages (Kasongan, Jipangan, Gendeng and Lemahdadi) are the objects of this research with the consideration that these villages have the potentials and capacity to be studied and developed as role models because of (1) their positions as the location of the tourist villages which are geographically located in Bantul district DIY that shows that the concept of ecotourism offers craft tourism in rural areas and the tourism is managed residents themselves; and (2) the idea of a creative economy will make sense if it has benchmarks that are developed starting from the smallest area of community livelihood, namely villages. The tourist villages will be the foundation for the creative economy to ignite through efforts to strengthen sustainable ecological-based tourism resources. The results of this study will be an initial review for designing a craft village empowerment strategy with the ecotourism concept as a new trend for the creative economy in Indonesia. Keywords: ecotourism, village, creative economy